Analysis of Exhaust Gas Emission of Motor Vehicles with Variations of Fuel Types - Isra Suryati; Ivan Indrawan; Jonathan Samuel Lubis; Munir Tanjung; Lies Setyowaty (Universitas Diponegoro, 2023)
The discrepancy between the use of vehicle fuel types and the vehicle's technical specifications is expected to affect exhaust emissions. This study aims to examine the effect of using four types of fuel with different octane number specifications on two four-wheeled motor vehicles with an EFI fuel delivery system on exhaust gas emission parameters of carbon monoxide (CO), hydrocarbon (HC), carbon dioxide (CO2) and non-emitting gases Oxygen (O2). With a quantitative experimental approach method using the Automotive Emission Analyzer and simple linear regression analysis, the results showed that the use of variations with octane numbers RON 98, RON 92, RON 90, and RON 88 fuels at the same time as variations in engine speed (1000 – 3000) RPM showed an effect on concentration. HC and CO emissions decreased with each increase in the octane number of fuel, RON 92 fuel with the lowest average CO / HC (0.0013% / 0.46 ppm) and RON 98 with the lowest average CO / HC (0.0026% / 0 ppm). The use of RON 92 fuel is more effective and inexpensive to apply to vehicles with an EFI fuel delivery system (with compression of 1:10/10.2) compared to RON 98 fuel which emits higher CO and HC emissions at low engine speed (1000 -1500) RPM.